Conjugacy classes and commuting probability in finite metacyclic P- groups - Moradipour, Kayyan (2012)
Let G be a finite non-abelian metacyclic p-group where p is any prime. We compute the exact number of conjugacy classes and the commutativity degree of G. In particular, we describe the number of conjugacy classes both in the split and non-split case.